Perceived Benefits and Harms of Involuntary Civil Commitment for Opioid Use Disorder. Issue 4 (December 2020) - Evans, Elizabeth A.; Harrington, Calla; Roose, Robert; Lemere, Susan; Buchanan, David
Involuntary civil commitment (ICC) to treatment for opioid use disorder (OUD) prevents imminent overdose, but also restricts autonomy and raises other ethical concerns. Using the Kass Public Health Ethics Framework, we identified ICC benefits and harms. Benefits include: protection of vulnerable, underserved patients; reduced legal consequences; resources for families; and "on-demand" treatment access. Harms include: stigmatizing and punitive experiences; heightened family conflict and social isolation; eroded patient self-determination; limited or no provision of OUD medications; and long-term overdose risk. To use ICC ethically, it should be recognized as comprising vulnerable patients worthy of added protections; be a last resort option; utilize consensual, humanizing processes; provide medications and other evidence-based-treatment; integrate with existing healthcare systems; and demonstrate effective outcomes before diffusion. ICC to OUD treatment carries significant potential harms that, if unaddressed, may outweigh its benefits. Findings can inform innovations for ensuring that ICC is used in an ethically responsible way.